Spatial modulation for multiple antenna wireless system - Lim, Sing Yee (2015)
In current times, the main stay in wireless technology is the Multiple – Input – Multiple – Output (MIMO) systems. With the increasing demand in the capabilities of wireless communication system, MIMO is thoroughly studied and developed in order to meet the demand. With that demand in mind, the purpose of this project is to research a new MIMO modulation technique to which is known as Spatial Modulation. This form of modulation utilizes the advantages of MIMO technology while at the same time keeping the cost low and sophisticated of implementing this system. This project will examine the performance of the MIMO system when subjected to varies channel conditions and tested with different number of transmitting-receiving antennas.